Penerapan 3R Melalui Inovasi Biopori Botol Plastik Bekas untuk Penanganan Sampah di Negeri Haruru - Jusuf Leiwakabessy; Sherly Lewerissa; Richardozn da Ressureição da Silva Moningka; Melky Laisila; Joybida Arnold Loppies; Farrel Evan Hehakaya (Fakultas Teknik Universitas Cenderawasih, 2026)
Negeri Haruru in Central Maluku Regency currently faces dual environmental challenges: unmanaged household organic waste and the frequent occurrence of surface water puddles during periods of high rainfall. This community service activity aims to educate and provide practical skills to junior high school students in Negeri Haruru regarding the implementation of 3R principles (Reduce, Reuse, Recycle) through the innovation of Biopore Infiltration Holes (LRB) using recycled plastic bottles as a cost-effective alternative to conventional liners. This innovation is designed to reduce plastic waste while simultaneously managing organic waste and improving soil water infiltration capacity independently at the household level. The implementation method involved participatory socialization, interactive discussions, and hands-on demonstrations of constructing biopore installations. The results indicated a significant increase in students' understanding of the role of soil fauna as decomposing agents and their technical ability to assemble used plastic bottles into functional biopore modules. The implementation of this innovation proved effective in maintaining the structural integrity of the infiltration holes and facilitating the biological decomposition of organic waste into compost. This program is expected to serve as a sustainable community-based environmental management model to minimize puddles and address waste problems in Negeri Haruru through a low-cost, appropriate technology approach.